Obvladovanje kreditnega tveganja pri bančnem poslovanju - Oplotnik, Žan Jan (Institute for Local Self-Government and Public Procurement Maribor, 2013)
Risk in banking business can not be avoided because the latter is strongly embedded in the very nature of it and banks should therefore be aware of the importance of effective risk management, encompassing the identification, measurement and assessment of each type of risk. Risk management can be important source of gaining competitive advantage and a way to survive in the world of banking. One of the most important risk in bank is the credit risk. Credit risk can be defined as the potential that a bank borrower or counterparty will fail to meet its obligations. The goal of credit risk management is to maximise bank´s risk-adjusted rate of return by maintaining credit risk exposure within acceptable parameters. Banks need to manage the credit risk inherent in the entire portfolio as well as the risk in invidual credits of transaction. Banks should also consider the relationships between credit risk and other risks. The effective management of credit risk is a comprehensive component of a comprehensive approach to risk management and essential to the long-term success of bank. Risk management is usualy regulated by bank directives, prescriptions, where the most important in Slovenia is the Law about banking with under law acts.